2022
DOI: 10.1111/jfpp.16330
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics, chemical, and bioactive compounds of yellow sweet pepper as affected by processing conditions

Abstract: Sweet peppers (Capsicum annuum L.) are vegetable crops that possess varied aroma, color, flavor, nutritional and medicinal value (Melgar-Lalanne et al., 2017). In the last few years, sweet peppers gained the attention of researchers due to the presence of an ample amount of phytochemicals such as phenols, antioxidants, carotenoids, flavonoids, and fiber that impart neutraceutical properties. Thus, sweet pepper represents a source of beneficial compounds, which makes it a good antioxidant additive for food and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…e drying rates were higher with the increase in drying temperature, and the time required for drying to occur for the same value of moisture content ratio increases as the drying temperature decreases. Similar behaviors were reported by Geng et al [28] when studying the drying kinetics of fresh peppers and Kaur et al [29] when studying the drying kinetics of sweet pepper. e slope of the curvature increases with increasing drying temperature and represents the fastest reduction in moisture content.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…e drying rates were higher with the increase in drying temperature, and the time required for drying to occur for the same value of moisture content ratio increases as the drying temperature decreases. Similar behaviors were reported by Geng et al [28] when studying the drying kinetics of fresh peppers and Kaur et al [29] when studying the drying kinetics of sweet pepper. e slope of the curvature increases with increasing drying temperature and represents the fastest reduction in moisture content.…”
Section: Resultssupporting
confidence: 83%
“…Xie et al [42] observed values close to the present study of 54.30 kJ•mol − 1 for Wolfberry (Lycium barbarum, L.) at temperatures of 60, 65, and 70 °C. Kheto et al [29] reported for sweet pepper (Capsicum annuum L.) at temperatures of 40, 50, and 60 °C activation energy of 22,256, 22,281, and 22,281…”
Section: Resultsmentioning
confidence: 99%
“…in the total polyphenol content [ 37 ]. Also, in a study by Kaur et al in 2005 [ 38 ], it was shown that the total polyphenol content of yellow sweet ‘Bachata’ bell peppers ( Capsicum annuum L.) that were subjected to hot-air convection drying (at three different temperatures of 40, 50, and 60 °C) was reduced from 784.01 mg GAE/100 g d.b. to 630.76 mg GAE/100 g d.b.…”
Section: Resultsmentioning
confidence: 99%
“…Three mathematical models (Henderson and Pabis model, Newton model, Page model) ( Kaur et al, 2022 , Macedo et al, 2020 , Türkmen Erol, 2021 ) for the optimal drying method were conducted to predict the drying characteristics. Three drying kinetic models were tested as follows ( Babalis et al, 2006 ): Where t was drying duration; a, k, n were undetermined coefficients.…”
Section: Methodsmentioning
confidence: 99%